Molecular dynamics simulation of the elliptical vibration-assisted machining of pure iron. Issue 1 (May 2018) - Goel, Saurav; Martinez, Fabian Duarte; Chavoshi, Saeed Zare; Khatri, Neha; Giusca, Claudiu
Abstract: It is well known that diamond wears out rapidly (within several metres of cutting length) when machining low carbon ferrous alloys and pure iron. The past few years have seen a growing interest in the field of elliptical vibration-assisted machining (EVAM) due to it being successful in the micromachining of difficult-to-cut materials including steel. During EVAM, a cutting tool is prescribed an oscillatory motion perpendicular to the direction of cutting, thereby causing the tool to be relieved intermittently from chemical and physical contact with the workpiece. This phenomenon serves as a guideline to develop the simulation test bed for studying EVAM in this work to compare it with conventional cutting. The pilot implementation of the EVAM came as a quasi-3-dimensional (Q3D) elliptical cutting model of body-centred cubic (BCC) iron with a diamond cutting tool using molecular dynamics (MD) simulation. The developed MD model supplemented by the advanced visualization techniques was used to probe the material removal behaviour, the development of the peak stress in the workpiece and the way the cutting force evolves during the cutting process. One of the key observations was that the cutting chips of BCC iron during conventional cutting underwent crystal twinning and became polycrystalline, while EVAM resulted in cutting chips becoming highly disordered, leading to better viscous flow compared to conventional cutting.